10.1016/s1558-0164(11)70452-7 (CrossRef Listing of Deleted DOIs, 2000)
Objective We aimed to determine the risk of subsequent seizure or epilepsy diagnosis after acute symptomatic seizures (ASyS) in critically ill children, evaluate whether antiseizure medication (ASM) use is associated with subsequent seizure/epilepsy diagnosis, and develop a simple Seizure/Epilepsy Risk Score to predict subsequent seizure/epilepsy diagnosis. Methods This was a prospective observational cohort study of consecutive children with acute encephalopathy undergoing clinically indicated continuous electroencephalographic (CEEG) monitoring in a pediatric intensive care unit. Patients with pre-existing epilepsy were excluded. Follow-up data were obtained to assess subsequent seizure/epilepsy diagnoses. Multivariable logistic regression and time-to-event analyses were used. Propensity score methods using inverse probability of treatment-weighted logistic regression were used to evaluate the association between discharge ASM use and subsequent seizure/epilepsy diagnoses. Results Among 365 patients with follow-up, a subsequent seizure/epilepsy diagnosis occurred in 64%. Subsequent seizure/epilepsy diagnosis was strongly associated with clinical seizures or status epilepticus prior to CEEG (odds ratio [OR] = 8.03, 95% confidence interval [CI] = 4.64-13.88), electrographic seizures or status epilepticus during CEEG (OR = 6.13, 95% CI = 2.36-15.91), and ASM administration during the admission (OR = 3.22, 95% CI = 1.79-5.80). A four-variable Seizure/Epilepsy Risk Score demonstrated generally increasing risk (13%-96%) with good discrimination (area under the receiver operating characteristic curve = .81). After propensity score adjustment, patients discharged on ASM had similar risk of subsequent seizure/epilepsy diagnosis compared with those discharged off ASM (inverse probability of treatment weighting-adjusted OR = 1.03, 95% CI = .61-1.72, p = .92). Significance Subsequent seizure or epilepsy diagnoses are common after ASyS in critically ill children and are strongly associated with acute clinical and electrographic seizure occurrence. A simple Seizure/Epilepsy Risk Score predicted subsequent seizure or epilepsy diagnoses, supporting early risk stratification. Patients discharged on or off ASM had a similar risk of subsequent seizure or epilepsy diagnoses.